Taḥlīl al-Ārāʾ al-Naḥwiyyah li al-Syaikh al-ʿUtsaimīn wa Manhajuhu fī ʿArḍ al-Qawāʿid al-Naḥwiyyah: تحليل الآراء النحوية للشيخ العثيمين ومنهجه في عرض القواعد النحوية - Muhamad Rizki (Ukazh : Journal of Arabic Studies, 2026)
The science of Arabic Nahwu plays a crucial role in accurately understanding the Qur’an and Hadith, as precise syntactic analysis determines the meaning of Sharʿi texts. Therefore, an applicative and contextual approach to teaching Nahwu is essential in Islamic education. This study analyzes the thought of Shaykh al-ʿUtsaimin and his method of presenting grammatical rules as exemplified in Sharḥ al-Ājurūmiyyah and Sharḥ Alfiyah Ibn Mālik. This research employs a qualitative library approach with a descriptive-analytical method. The primary data sources are the two commentaries, supported by relevant secondary literature. The findings show that Shaykh al-ʿUtsaimin grammatical thought integrates precise syntactic analysis with a pedagogical orientation using a deductive approach. Nahwu is positioned as a functional instrumental science for understanding Sharʿi texts, with the Qur’an and Hadits as the main linguistic references. In addressing grammatical disagreements, he applies the principle of preference (Tarjiḥ) based on clarity of Iʿrab, strength of syntactic meaning, and ease of comprehension, without strict adherence to Basrah or Kufah schools. Methodologically, rules are presented systematically through concise definitions, representative examples, structured Iʿrab analysis, and a balanced presentation of scholarly differences.